A CoO with a hybrid structure of flocculent and regular hexagonal structures x -CuO catalyst and its preparation method and use
CoOx-CuO catalyst with a flocculent and regular hexagonal hybrid structure was prepared through hydrothermal reaction and calcination treatment, which solved the problem of high cost of precious metal catalysts and easy agglomeration of transition metal oxide catalysts, and achieved efficient hydrolysis and hydrogen production catalysis Activity and hydrogen release rate.
Patent Information
- Application Number
- CN202410422371.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-09
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2044-04-09
AI Technical Summary
In the prior art, the high cost of precious metal catalysts and the small amount of natural resource storage limit their large-scale use, and transition metal oxide catalysts are prone to agglomeration when used alone, resulting in loss of activity.
Cobalt copper precursors were prepared by hydrothermal reaction and calcined at 600-680°C for 2-5 hours to obtain a CoOx-CuO catalyst with a flocculent and regular hexagonal hybrid structure.
This catalyst not only improves catalytic activity and hydrolysis, but also the synergistic effect between the introduction of Cu and CoOx significantly increases the hydrogen discharge rate of SB solution under alkaline conditions.
Smart Images

Figure HDA0004782886610000011 
Figure HDA0004782886610000021 
Figure HDA0004782886610000031
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of catalysts, and particularly relates to a CoO catalyst having a flocculent and regular hexagonal hybrid structure. x -CuO catalyst and its preparation method and use. Background Art
[0002] As an economical and efficient green energy carrier, hydrogen energy has a series of advantages such as abundant sources, clean and environmentally friendly, high calorific value, no pollution, and can be stored and transported. It is considered to be an ideal substitute for traditional carbon-based fossil energy, which is of great significance to solving the traditional carbon-based fossil energy and environmental problems facing the world. It is generally believed that the safe and effective storage of hydrogen is one of the main bottlenecks faced by its industrial-scale application. In the past few decades, many efforts have been devoted to the development of new hydrogen storage strategies. Among them, chemical hydrides (such as sodium borohydride (NaBH4, SB) and ammonia borane (NH3BH3, AB)) hydrogen storage has attracted widespread attention due to its high safety, high efficiency and high hydrogen storage density. As one of the representative chemical hydrides, SB is non-flammable at room temperature, stored in solid and alkaline solutions, and has the advantages of high stability, safe storage and transportation. In addition, under the catalysis of suitable catalysts, 1g SB can produce 0.108g H2 through a hydrolysis process, and the mass hydrogen storage density is as high as 10.8wt%, which can meet the on-demand hydrogen production. In addition, the byproduct NaBO2 produced during the hydrolysis process is environmentally friendly and easy to recycle into reactants. Based on these advantages, SB hydrolysis technology can be used to integrate hydrogen production, storage and transportation into a production chain.
[0003] However, the development of suitable SB hydrolysis catalysts is one of the most critical issues that must be addressed for the large-scale application of this technology. Initially, noble metals or alloys such as Ru, Rh, Pt and Pd showed excellent catalytic performance in the hydrolysis reaction and were the main catalysts in the SB hydrolysis literature, but the high cost and small reserves of natural resources limited the large-scale use of noble metal catalysts. Therefore, it is crucial to develop inexpensive catalysts with high catalytic activity to replace these noble metal-based catalysts. Transition metal oxides (TMOs) are considered to be one of the most promising alternatives to noble metal catalysts due to their unique electronic structure and physicochemical properties. Among transition metal oxides, cobalt-based and copper-based oxides (Co3O4, CoO, CuO and Cu2O) have attracted widespread attention in the field of catalytic hydrolysis due to their advantages such as low cost, high redox chemical activity and a wide range of oxidation states.
[0004] At present, a variety of methods have been proposed to design and modify cobalt-based and copper-based oxides to have excellent catalytic properties: on the one hand, it aims to increase the number of active sites, such as metal loading or doping, improving crystal size, and increasing specific surface area, and on the other hand, it aims to develop nanostructured catalysts with various morphologies, such as porous structures, nanospheres, and nanosheets. Although these nanostructured catalysts can produce hydrogen on demand in NaBH4 alkaline solutions, they are prone to agglomeration during single use, resulting in loss of activity and inactivity. Summary of the invention
[0005] In view of the above-mentioned deficiencies in the prior art, the present invention provides a CoO having a flocculent and regular hexagonal hybrid structure. x -CuO catalyst and preparation method and use thereof, the CoO x -CuO catalysts can not only effectively solve the problem of poor catalyst activity, but also provide a clearer understanding of the catalytic behavior between oxide composite catalysts, and provide possibilities for the design and development of other high-performance, low-cost catalysts.
[0006] To achieve the above purpose, the technical solution adopted by the present invention to solve the technical problem is:
[0007] A CoO with a hybrid structure of flocculent and regular hexagonal structures x -CuO catalyst preparation method, the specific process is: prepare cobalt copper precursor by hydrothermal reaction, and then calcine at 600-680℃ for 2-5h to obtain CoO with flocculent and regular hexagonal hybrid structure x -CuO catalyst.
[0008] Furthermore, the calcination temperature is 600° C. and the calcination time is 2 to 3 hours.
[0009] Furthermore, the calcination temperature is 600° C. and the time is 2 h.
[0010] Further, the preparation method of the cobalt-copper precursor is as follows:
[0011] Cobalt salt, copper salt, CO(NH2)2, NH4F and water are mixed and subjected to hydrothermal reaction. After the reaction is completed, the reaction product is taken out, washed and dried to obtain a precursor.
[0012] Furthermore, the molar ratio of cobalt salt, copper salt, CO(NH2)2 and NH4F is 1-2:1-2:5-10:5-8.
[0013] Furthermore, the molar ratio of cobalt salt, copper salt, CO(NH2)2 and NH4F is 2:2:10:8.
[0014] Furthermore, the cobalt salt is CoCl2·6H2O.
[0015] Furthermore, the copper salt is CuCl2·2H2O.
[0016] Furthermore, the hydrothermal reaction temperature is 120° C. and the reaction time is 6 h.
[0017] Furthermore, the hydrothermal reaction product was washed with deionized water and ethanol for 3-5 times in sequence, and then vacuum dried at 80° C. for 6 h.
[0018] A CoO with a hybrid structure of flocculent and regular hexagonal structures x -CuO catalyst is prepared by the above method.
[0019] The above CoO x -Application of CuO catalyst in hydrogen production by hydrolysis.
[0020] Beneficial effects of the present invention:
[0021] 1. The catalyst in the present application is prepared by a hydrothermal method and calcination treatment. The catalyst has the advantages of simple preparation method, convenient process, easy operation, low cost and no pollution. The calcination process can change the crystallization properties of the catalyst, increase the hydrolysis of the catalyst, and thus improve the catalytic activity of the catalyst and improve the catalytic effect.
[0022] 2. The catalyst in this application has a unique flocculent and regular hexagonal hybrid structure after calcination, which is better than CuO and CoO prepared under the same conditions. x Hybrid catalyst, the introduction of Cu can improve CoO x -CuO reduces the hydrogen desorption rate of SB solution under alkaline conditions. This is because the positive synergistic effect between Co and Cu enhances their catalytic activity, thereby improving the catalytic activity in the process of hydrolysis to produce hydrogen and increasing the hydrogen desorption rate. BRIEF DESCRIPTION OF THE DRAWINGS
[0023] Figure 1 is a SEM image of the catalyst prepared in Example 1;
[0024] Figure 2 is a SEM image of the catalyst prepared in Comparative Example 1;
[0025] Figure 3 is a SEM image of the catalyst prepared in Comparative Example 2;
[0026] Figure 4 This is the SEM image of the catalyst prepared in Comparative Example 3;
[0027] Figure 5 is the EDS mapping diagram of the catalyst prepared in Example 1;
[0028] Figure 6This is the XPS graph of the catalyst prepared in Example 1;
[0029] Figure 7 is a graph of hydrogen release rate of the catalyst prepared in Example 1;
[0030] Figure 8 The hydrogen release rate diagram of the catalysts prepared at different calcination temperatures;
[0031] Fig. 9 Figure 2 shows the three different catalysts CoO obtained under the same preparation conditions (hydrothermal: 120 °C calcination: 600 °C). x -CuO, CoO x And the hydrogen desorption performance of CuO in SB alkaline solution. DETAILED DESCRIPTION
[0032] The specific implementation modes of the present invention are described below so that those skilled in the art can understand the present invention. However, it should be clear that the present invention is not limited to the scope of the specific implementation modes. For those of ordinary skill in the art, as long as various changes are within the spirit and scope of the present invention as defined and determined by the attached claims, these changes are obvious, and all inventions and creations utilizing the concept of the present invention are protected.
[0033] Example 1
[0034] A CoO with a hybrid structure of flocculent and regular hexagonal structures x -The preparation method of CuO catalyst, the specific process is as follows:
[0035] 2mmol CoCl2·6H2O, 2mmol CuCl2·2H2O, 10mmol CH4N2O, 8mmol NH4F and 30ml deionized water were mixed to obtain a blue solution. Subsequently, the blue solution was transferred to a 50mL reactor with a polytetrafluoroethylene liner, placed in a drying oven and reacted at a hydrothermal reaction temperature of 120°C for 6h. After the reactor was naturally cooled to room temperature, the hydrothermal product was washed 3 times with deionized water and anhydrous ethanol each. The hydrothermal product was dried at 80°C for 6h and ground into powder, which was CoO x -CuO precursor.
[0036] Finally, the obtained CoO x -CuO precursor was placed in a tube furnace under Ar atmosphere at 5℃·min -1 The temperature was raised from room temperature to 600°C calcination temperature and heated at 600°C for 2h. The product was slowly cooled to room temperature and ground to obtain black powder, and CoO with a flocculent and regular hexagonal hybrid structure was obtained. x -CuO catalyst.
[0037] Example 2
[0038] A CoO with a hybrid structure of flocculent and regular hexagonal structures x -The preparation method of CuO catalyst, the specific process is as follows:
[0039] 2mmol CoCl2·6H2O, 2mmol CuCl2·2H2O, 10mmol CH4N2O, 8mmol NH4F and 30ml deionized water were mixed to obtain a blue solution. Subsequently, the blue solution was transferred to a 50mL reactor with a polytetrafluoroethylene liner, placed in a drying oven and reacted at a hydrothermal reaction temperature of 110°C for 6h. After the reactor was naturally cooled to room temperature, the hydrothermal product was washed 3 times with deionized water and anhydrous ethanol each. The hydrothermal product was dried at 80°C for 6h and ground into powder, which was CoO x -CuO precursor.
[0040] Finally, the obtained CoO x -CuO precursor was placed in a tube furnace under Ar atmosphere at 5℃·min -1 The temperature was raised from room temperature to 620°C calcination temperature and heated at 620°C for 2h. The product was slowly cooled to room temperature and ground to obtain black powder, thus obtaining CoO with a flocculent and regular hexagonal hybrid structure. x -CuO catalyst.
[0041] Example 3
[0042] A CoO with a hybrid structure of flocculent and regular hexagonal structures x -The preparation method of CuO catalyst, the specific process is as follows:
[0043] 2mmol CoCl2·6H2O, 2mmol CuCl2·2H2O, 10mmol CH4N2O, 8mmol NH4F and 30ml deionized water were mixed to obtain a blue solution. Subsequently, the blue solution was transferred to a 50mL reactor with a polytetrafluoroethylene liner, placed in a drying oven and reacted at a hydrothermal reaction temperature of 120°C for 6h. After the reactor was naturally cooled to room temperature, the hydrothermal product was washed 3 times with deionized water and anhydrous ethanol each. The hydrothermal product was dried at 80°C for 6h and ground into powder, which was CoO x -CuO precursor.
[0044] Finally, the obtained CoO x -CuO precursor was placed in a tube furnace under Ar atmosphere at 5℃·min -1The temperature was raised from room temperature to 650°C calcination temperature and heated at 650°C for 3h. The product was slowly cooled to room temperature and ground to obtain black powder, thus obtaining CoO with a flocculent and regular hexagonal hybrid structure. x -CuO catalyst.
[0045] Comparative Example 1
[0046] Compared with Example 1, the calcination temperature in this example is set to 400°C, and the rest of the process is consistent with Example 1.
[0047] Comparative Example 2
[0048] Compared with Example 1, the calcination temperature in this example is set to 500° C., and the rest of the process is consistent with Example 1.
[0049] Comparative Example 3
[0050] Compared with Example 1, the calcination temperature in this example is set to 700° C., and the rest of the process is consistent with Example 1.
[0051] Comparative Example 4
[0052] Compared with Example 1, the calcination temperature in this example is set to 300° C., and the rest of the process is consistent with Example 1.
[0053] Experimental example
[0054] 1. The morphology of the catalysts prepared in Example 1 and Comparative Examples 1 to 3 was detected, indicating that the synthesis method can obtain a mixture of CoOx-CuO with a flocculent and regular hexagonal structure, and part of CoOx is attached to the surface of CuO, which can better enable the synergistic effect between the oxides. The SEM image is shown in Figures 1 to 4 . Figure 1 These are SEM images of the catalyst prepared in Example 1 of the present application at different magnifications, A is a 500x SEM image, B is a 5000x SEM image, and C is a 100000x SEM image.
[0055] like Figures 1 to 4 As shown, only by adopting the technical solution defined in the present application can a catalyst having both flocculent and regular hexagonal hybrid structures be prepared.
[0056] 2. The catalyst prepared in Example 1 was analyzed by element distribution and XPS spectra. Figure 5 and 6 .
[0057] As shown in the figure, the EDS Mapping element diagram of the flocculent and regular hexagonal structure shows the distribution of C, O, Co and Cu elements, indicating that the main components of the flocculent structure are (Co3O4 and CoO), and the main component of the hexagonal structure is CuO. x The element composition and valence state of the CuO catalyst were analyzed and studied. x The full spectrum of -CuO confirms the coexistence of C, O, Co and Cu elements, and proves that the addition of Cu makes CoO x A positive synergistic effect occurs between the oxide and CuO, which reduces the catalytic energy barrier and thus enhances the x -CuO hybrid oxide catalyst dehydrogenation ability. Therefore, the introduction of CuO is considered to be an effective way to adjust the electronic structure between metal oxide-Co3O4 and improve the catalytic activity of NaBH4 hydrolysis.
[0058] 3. Hydrogen production by hydrolysis was carried out using the catalysts prepared in Example 1 and Comparative Examples 1 to 4. The hydrogen release performance test conditions were: 10 ml of 1 wt% NaOH + 1 wt% NaBH4 solution, and the hydrolysis reaction temperature was 40°C. All recorded hydrogen production (mL) was converted to volume at 25°C using the ideal gas equation. The hydrogen release rate (HGR) is the ratio of the hydrogen volume (ml) to the product of the linear reaction time (min) and the catalyst weight (g) at 25°C, in units of mL·min -1 ·gcat -1 The results are shown in Figure 7 as well as Figure 8 .
[0059] like Figure 7 As shown, with the increase of CoO x -CuO hybrid oxide catalyst dosage increased (0.01-0.04 g), it is clear that the NaBH4 hydrogen production is basically the same. HGR gradually increases linearly, which indicates that CoO x The amount of -CuO hybrid oxide catalyst is linearly correlated with the hydrolysis rate of NaBH4.
[0060] like Figure 8 As shown, with the increase of calcination temperature, the HGR of the catalyst reaches the maximum at 600°C, indicating that the calcination temperature has a certain effect on the HGR of the catalyst.
[0061] Fig. 9 The three different catalysts CoO obtained under the same preparation conditions (hydrothermal: 120 °C calcination: 600 °C) are shown. x -CuO, CoO xThe hydrogen release performance of CuO and SB alkaline solution. The addition amount of catalyst is 0.02g. It can be seen from the figure that CuO catalyst has very low activity for SB hydrolysis. x The catalyst has a certain catalytic activity for the hydrolysis of SB, but the reaction rate is very slow in the first 60 seconds, and it takes 8 minutes to completely release hydrogen. x Formation of CoO x -CuO hybrid catalysts showed very high catalytic activity, which clearly showed that CuO and CoO x There is a positive synergistic effect between them, which significantly improves the catalytic performance.
[0062] Finally, it should be noted that the above specific implementation methods are only used to illustrate the technical solution of the present invention rather than to limit it. Although the present invention has been described in detail with reference to examples, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the spirit and scope of the technical solution of the present invention, which should be included in the scope of the claims of the present invention.
Claims
1. A CoO with a hybrid structure of flocculent and regular hexagonal structures x -CuO catalyst preparation method, characterized in that, The cobalt-copper precursor was prepared by hydrothermal reaction and then calcined at 600-680℃ for 2-5h to obtain CoO with flocculent and regular hexagonal hybrid structure. x -CuO catalyst; The preparation method of the cobalt-copper precursor is as follows: Cobalt salt, copper salt, CO(NH2)2, NH4F and water are mixed and subjected to hydrothermal reaction. After the reaction is completed, the reaction product is taken out, washed and dried to obtain a precursor.
2. The preparation method according to claim 1, characterized in that: The calcination temperature is 600℃ and the time is 2~3h.
3. The preparation method according to claim 2, characterized in that: The calcination temperature is 600°C and the time is 2h.
4. The preparation method according to claim 1, characterized in that: The molar ratio of cobalt salt, copper salt, CO(NH2)2 and NH4F is 1~2:1~2:5~10:5~8.
5. The preparation method according to claim 4, characterized in that: The molar ratio of cobalt salt, copper salt, CO(NH2)2 and NH4F is 2:2:10:
8.
6. The preparation method according to claim 4 or 5, characterized in that: The cobalt salt is CoCl2·6H2O.
7. The preparation method according to claim 4 or 5, characterized in that: The copper salt is CuCl2·2H2O.
8. A CoO with a hybrid structure of flocculent and regular hexagonal structures x -CuO catalyst, characterized in that The method is prepared by any one of claims 1 to 7.
9. CoO according to claim 8 x -Application of CuO catalyst in hydrogen production by hydrolysis of NaBH4.
Citation Information
Patent Citations
Hydrolysis hydrogen production catalyst as well as preparation method and application thereof
CN115007152A